Virtual test bench for the design of control strategies for water heaters - Quintã, André F. (2022)
An innovative methodology and a virtual test bench (VTB) are proposed to support the design of water heaters’control strategies. This platform allows to speed up the development and evaluation of control systems even before the existence of prototypes or real test environments. By simulating the environmental conditions and the state of the different device components, it will be possible to detect and correct possible initial errors in the control system design which can be time consuming and costly due to subsequent modifications to the system or equipment components. The architecture of the proposed system establishes four operating modes: open-loop data acquisition, real-time simulation, hardware-in-the-loop simulation, and test of the complete real system, the incorporation of these functionalities in the same platform is not reported in the literature for domestic water heaters. The virtual test bench was designed to accommodate different water heaters including, but not limited to, gas, electric, and heat pumps, for instantaneous hot water production or including hot water storage. The prototype of the virtual test bench is described emphasizing the hardware-in-the-loop methodologies and embedded control. The particular case study of a tankless gas water heater (TGWH) is presented implementing the different operation modes in the virtual test bench. The water heater models, control strategies, simulation, and experimental data are presented and discussed.